1974
DOI: 10.1126/science.186.4161.359
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma: Drug-Induced Differentiation Increases Proportion of Cytoplasmic RNA That Contains Polyadenylic Acid

Abstract: The production of cytoplasmic RNA that contains polyadenylic acid is increased, relative to total cytoplasmic RNA, in a neuroblastoma clone, NBE-(A), after induction of differentiation by 4-(3-butoxy-4-methoxybenzyl)-2-imidazolidinone, an inhibitor of adenosine 3',5'-monophosphate phosphodiesterase. The amount of RNA that contains polyadenylic acid in cytoplasm may be greater in such differentiated neuroblastoma cells than in proliferating control cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Although PGE1 and R020-1724 induce many differentiated functions in neuroblastoma cells in a similar manner, (Furmanski, Silverman andLubin, 1971, Prasad andKumar, 1974) PGE1 appears to change characteristically the expression of AK and G6PD,6PGD and LDH. From these data it is clear that PGE1-treated neuroblastoma cells in culture express different enzyme patterns from those cells which were treated with R020-1724. Previous studies have shown that many differentiated functions in neuroblastoma cells are induced both by PGE1 andR020-1724 (Furmanski et al, 1971;Prasad and Kumar, 1974).…”
Section: In Vitro Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Although PGE1 and R020-1724 induce many differentiated functions in neuroblastoma cells in a similar manner, (Furmanski, Silverman andLubin, 1971, Prasad andKumar, 1974) PGE1 appears to change characteristically the expression of AK and G6PD,6PGD and LDH. From these data it is clear that PGE1-treated neuroblastoma cells in culture express different enzyme patterns from those cells which were treated with R020-1724. Previous studies have shown that many differentiated functions in neuroblastoma cells are induced both by PGE1 andR020-1724 (Furmanski et al, 1971;Prasad and Kumar, 1974).…”
Section: In Vitro Systemmentioning
confidence: 99%
“…We have shown that the muscletype lactate dehydrogenase (LDH-5) which prevails in embryonic tissue (Wolf and Engel,1.972) is present in neuroblastoma cells, but absent from mouse brain tissue , indicating the re-expression of an embryonic feature during malignant transformation. In addition, it has been reported (Bondy, Prasad and Purdy, 1974) that the amount of poly-adenylic-(A)-containing cytoplasmic RNA is greater in cAMP-induced " differentiated" neuroblastoma cells than that in malignant cells. These data indicate that there may be an alteration in the expression of genetic information during the time of " differentiation " of neuroblastoma cells in culture.…”
mentioning
confidence: 99%
See 3 more Smart Citations